Directions for Reducing Pesticide Pressure on Agro-Landscapes - Hadzalo Yaroslav; Likar Yaroslav; Beknozarova Zamira (BIO Web of Conferences)
Measures have been developed to reduce chemical pesticide pressure on the environment. The impact of biopreparations on the productivity elements and seed quality of sunflower hybrids was determined. The application of the biopreparation Agat-25K was characterized by a direct positive influence on the increase in sunflower head diameter. For example, the hybrid Yason demonstrated an increase in this indicator by 15.2% due to the use of the Agat-25K biological protection method. Furthermore, Agat-25K contributed to a 4.6% increase in the weight of 1,000 seeds, with the hybrid Yason showing an average weight of 63.5 g, compared to the control (60.7 g). However, a decreasing trend in husk content was observed across all hybrids, averaging from 5.3% to 6.8%. The maximum average seed yield of 3.17 t/ha was produced by the hybrid Rimi, while yields decreased by 8.7% and 34.5% for the PR64E71 and Yason hybrids, respectively. Among the biopreparations, Agat-25K had an undeniable advantage, enhancing seed productivity by 16.4%–33.4%. In terms of oil yield per unit area, Rimi led with 1.66 t/ha, while PR64E71 and Yason recorded decreases of 10.9%–26.6%. Agat-25K also exhibited superiority in oil productivity.